Library cataloguing and multimedi libraries (Anmol Pubications, 2001)
Contents of material: Multimedia library. Cataloguing technologies. Managing the catalogue deparment. Multimedia resources. Oline services. Miltimedia medium. Multimedia catalogue and the computer. Online technical support systems